Koncepcje wartości patriotyzmu na tle historycznym (Filozofia Edukacji, 2019)
In the article, a historical development of the understanding of the value of patriotism in Poland is presented. The presentation ranges from the Middle Ages till present days. The views on patriotism advocated by the noblest Polish writers and intellectuals, the creators of Polish culture, are introduced. In the introduction, the author brings in several etymological and definitional considerations, noting that the entry “patriotism” is missing in the important sources of today’s Polish pedagogy. In the following points, representatives of the successive historical periods are portrayed and their views are illustrated by short quotations from their works. The author suggests that, from the very beginning, a characteristic trait of Polish patriotism were the values of dedication and sacrifice for the country. Neither did the values appear only in Romanticism, nor, similarly, did they disappear in Positivism or later on. In the author’s view, patriotism helped Poles in preserving their identity in the periods of partitions and Communist regime. Today the Polish patriotism should open itself to the universal values of humanity.